2015
DOI: 10.1021/cm502939r
|View full text |Cite
|
Sign up to set email alerts
|

Protonic and Electronic Transport in Hydrated Thin Films of the Pigment Eumelanin

Abstract: The electrical properties of eumelanin, a ubiquitous natural pigment, have fascinated scientists since the late 1960s. For several decades, the hydrationdependent electrical properties of eumelanin have mainly been interpreted within the amorphous semiconductor model. Recent works undermined this paradigm. Here we study protonic and electronic charge carrier transport in hydrated eumelanin in thin film form. Thin films are ideal candidates for these studies since they are readily accessible to chemical and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
206
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(224 citation statements)
references
References 58 publications
13
206
0
Order By: Relevance
“…[20][21][22] showing the relationship between protons as the major charge carrier and the paramagnetic species observed in eumelanin, with the phenomenon of photoconductivity in eumelanin also being accounted for in ref. 23.…”
Section: Conceptual Insightsmentioning
confidence: 99%
“…[20][21][22] showing the relationship between protons as the major charge carrier and the paramagnetic species observed in eumelanin, with the phenomenon of photoconductivity in eumelanin also being accounted for in ref. 23.…”
Section: Conceptual Insightsmentioning
confidence: 99%
“…1) would make eumelanin a mixed ionic-electronic material. [21,23,36] Wünsche et al proposed an explanation of the charge-carrier transport properties of hydrated eumelanin thin films included between metal electrodes with an interplay between proton migration, interfacial metal electrode/ eumelanin charge transfer (redox) processes, and electronic transport [37,38] (Fig. 4).…”
Section: Introductionmentioning
confidence: 99%
“…25 In this scenario, a number of studies have recently reported eumelanin based functional devices 14,26,27 as well as eumelanin films for nerve tissue engineering 23 and nonwoven fibers for cardiac tissue engineering. 19 In a systematic investigation some of us addressed the issue of eumelanin processability focusing on thin film fabrication with the main goal of obtaining both a complete chemical-structural control of the material and high quality film morphology.…”
Section: Introductionmentioning
confidence: 99%